2022
DOI: 10.1186/s11658-022-00319-7
|View full text |Cite
|
Sign up to set email alerts
|

Senescence-associated reprogramming induced by interleukin-1 impairs response to EGFR neutralization

Abstract: Background EGFR targeting is currently the main treatment strategy for metastatic colorectal cancer (mCRC). Results of different clinical trials show that patients with wild-type KRAS and BRAF benefit from anti-EGFR monoclonal antibodies (moAbs) cetuximab (CTX) or panitumumab. Unfortunately, despite initial response, patients soon became refractory. Tumor heterogeneity and multiple escaping routes have been addressed as the main culprit, and, behind genomic alterations already described, change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…In our work we explored the effect of cetuximab in colorectal cancer in vitro models and the antibody was able to increase senescence markers. In addition, our investigation also revealed that cetuximab was acting by inducing the production of the pro-inflammatory cytokine IL-1 and released in the microenvironment ( Romaniello et al, 2022 ). Considering the known role of IL-1 in inducing senescence, is tempting to consider it as one of the mechanisms of action for CTX, that will achieve a cell cycle arrest by immediate autocrine production of IL-1 ( Figure 2 ).…”
Section: Mechanisms Of Senescence In Egfr Inhibitionmentioning
confidence: 79%
See 3 more Smart Citations
“…In our work we explored the effect of cetuximab in colorectal cancer in vitro models and the antibody was able to increase senescence markers. In addition, our investigation also revealed that cetuximab was acting by inducing the production of the pro-inflammatory cytokine IL-1 and released in the microenvironment ( Romaniello et al, 2022 ). Considering the known role of IL-1 in inducing senescence, is tempting to consider it as one of the mechanisms of action for CTX, that will achieve a cell cycle arrest by immediate autocrine production of IL-1 ( Figure 2 ).…”
Section: Mechanisms Of Senescence In Egfr Inhibitionmentioning
confidence: 79%
“…These findings challenge the consolidated theory about senescence as the conclusion of the life cycle followed by permanent growth arrest, and unveil a dynamic post-senescence process, which represents a defy for therapeutical agents. Thus, the contemporary targeting of senescence by senotherapeutic drugs along with target therapy toward ERBB family members may boost the efficacy of future cancer treatment ( Zhu et al, 2015 ; Schafer et al, 2017 ; Ovadya and Krizhanovsky, 2018 ; Romaniello et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Small molecular inhibitors or monoclonal antibodies for EGFR signaling have been widely used for EGFR signaling-dependent malignancies [ 21 , 22 ]. A previous review [ 21 ] proposed the potential role of ARID1A as a novel biomarker for the response to EGFR-TKIs.…”
Section: Discussionmentioning
confidence: 99%